An analysis of the quantity and quality of tourism services in Zanjan province - mahdi charaghi; Hossein tahmasebi moghaddam; Mohammad Reza, Nemati; Saeed Nasiri Zare (تحقیقات کاربردی علوم جغرافیایی)
The advancement of tourism in any region necessitates a thorough understanding of the area's potential, alongside the provision of requisite facilities and services for tourists. Effective planning at all levels is essential to realize successful tourism development. This research investigates the challenges associated with service provision and ranks tourist destinations based on their tourism potential in Zanjan Province, Iran. The study employs a mixed-methods approach, integrating qualitative and quantitative techniques, with data gathered through interviews and questionnaires. Interview data were analyzed utilizing MaxQDA software, while the Analytical Hierarchy Process (AHP) was applied to evaluate criteria, and geographic modeling was employed to assess the spatial distribution of tourist destinations. The findings indicate that Zanjan Province, despite its considerable tourism potential, contends with multiple challenges, including inadequate facilities, inconsistent policies aimed at enhancing tourism services, and insufficient management and planning for tourism development. These challenges have impeded the province's progress in the tourism sector. Two primary concerns identified are the overall low level of services and the lack of coherence in planning and perspectives regarding tourism development. Nonetheless, the geographical distribution analysis identifies several high-potential tourist destinations, including Soltanieh Dome, Gen Chimneys, Angoran Mine, Oljaito Ecotourism Resort, Soltanieh Ecotourism Resort, Boutique Hotel, Zulfaqari Mansion, El Daghi, Seyed Mohammad Bridge, Zanjan Jame Mosque, Khedevi House, and the Colorful Mountains. These destinations, classified within the first cluster, are distinguished by their high tourism potential and accessibility, attributed to their unique features and proximity to populated areas. Consequently, they warrant prioritization in service planning and development initiatives. In conclusion, while Zanjan Province possesses substantial tourism potential, it is imperative to address systemic issues such as inadequate facilities, inconsistent policies, and poor management to foster sustainable tourism growth. Prioritizing high-potential destinations can establish a foundation for targeted development, enabling the province to enhance its tourism services, attract a greater number of visitors, and achieve long-term success within the tourism sector.